Aspects of meliponiculture with emphasis on the genus Scaptotrigona - Fernandes Gonçalves Benites, Alessandra; Smielevski de Souza, Tuan Henrique; Guadalin de Oliveira, Wendy; Leão Figueira , Cinthia; de Alencar Arnaut de Toledo, Vagner (Scientia Agraria Paranaensis, 2022)
Meliponiculture is the rational exploitation of stingless bees, in which different species of bees are exploited. This diversity ensures differences in morphological and biological aspects, nesting habits, resource gathering behaviors, defense and productivity. Knowledge of the aspects of this diversity of bees makes it possible to understand and disseminate technical-scientific information. However, the difficulty of obtaining knowledge in this area that is on the rise is something that hinders the dissemination of scientific knowledge. This review aims to disclose the importance of meliponiculture, its main aspects and emphasize the productive potential of the genus Scaptotrigona. This genus has productive potential and can be exploited commercially or as a research objective to increase production rates. Given the above, studies of the bionomic characteristics of meliponines are relevant for the economy, pollination services, conservation of plant and animal species, standardization of materials and equipment, in addition to enabling the establishment of adequate management, contributing to increased productivity.